A participatory approach to conservation: working with community to save the cultural hertiage of Panamnagar - Ahmed, Iftekhar (BRAC University, 2010)
Panamnagar is a unique township in Sonargaon thana of Narayanganj district of Bangladesh. It is stretched in a single street with street front houses on either side, which are of high architectural and archeological value. Due to lack of proper conservation plans, degradation caused by natural weathering, lack of maintenance and unplanned modification, many of the buildings face serious threat of losing the unique architectural features. Though declared a national heritage site, there is no definite mention about what constitutes the heritage of the area and how it should be conserved. Urban conservation is not about freezing time or even the new development and use. Rather it is best to set stage for the management of incremental changes. As compelling and historically valuable the place may be, it is the people and activities that breathe life in Panamnagar. With absence of any major initiative from the government, a “community-based” conservation process is the only possible solution to save the cultural heritage. This paper suggests the process of integrated public involvement in the conservation management plan for Panamnagar including steps, such as, understanding problems; generating options for response; evaluating the options; and ultimately choosing a roadmap for conservation management.